PERSEPSI GURU SEKOLAH DASAR TERHADAP PENGEMBANGAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA - rosmalah rosmalah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The purpose of this study was to determine Teacher Perceptions of Character Development in Thematic-Based Indonesian Language Learning in SD Mitra PGSD Watampone. The approach used in this study is a quantitative approach that is descriptive. The results showed the teacher's perception of student character development will have an impact on the ability of teachers to manage a learning that is directed not only to the development of aspects of student knowledge and skills but also facilitate students to have strong character. Character development of students tends to have a high level of difficulty because this aspect is very abstract and requires deep observation. The characters studied include responsibility, honesty, discipline, love and affection, and caring.